Characterising cheerfulness as a value for young people - A. M. Lesin (Вестник университета, 2022)
This article is presented the study’s results of the place of the cheerfulness value in the young people’s value-based world view. This value relates with the severity of value career orientations, significance of other instrumental, terminal ones, as well as with the significance, implementation and conflict between the significance and implementation of internal and external values. The value under study is to a greater extent associated with the personal sphere of young people, is not associated with the manifestation of their initiative and is negatively associated with some career orientations. The cheerfulness is an important, but rather a potential value, which does not have much motivational potential. The article suggests a hypothesis, that the image of a reliable person is negatively associated with emotionality and a positive attitude to life, and positively – with the manifestation of seriousness and will. It is concluded that this value is an internal value that is not associated with demonstrating their success to other people and social status, but is an indicator and consequence of their personal internal development and is more connected with warm friendly relationships and emotional richness of life.